FIGO Statement: Staffing requirements for delivery care, with special reference to low‐ and middle‐income countries. Issue 1 (12th April 2019) - Stones, William; Visser, Gerard H.A.; Theron, Gerhard
Abstract: International standards for clinical staffing of delivery care in maternity units are currently lacking, with resulting gaps in provision leading to adverse outcomes and very poor experiences of care for women and families. While evidence‐informed modelling approaches have been proposed based on population characteristics and estimated rates of complications, their application and outcomes in low‐resource settings have not been reported. Here, FIGO's Safe Motherhood and Newborn Health Committee proposes indicative standards for labor wards as a starting point for policy and program development. These standards consider the volume of deliveries, the case mix, and the need to match clinical care requirements with an appropriate mix of professional skills among midwifery and obstetric staff. The role of Shift Leader in busy labor wards is emphasized. Application of the standards can help to assure women and their families of a safe but also positive birthing experience. FIGO calls for investment by partners to test these clinically‐informed recommendations for delivery unit staffing at hospital and district level in low‐ and middle‐income country settings. Abstract : Staffing of maternity units for safe woman‐centered delivery care should be based on delivery numbers, case mix, and skill mix.